Exploring the Fundamental Factors Behind Algal-Bacterial Symbiosis and Their Impact on Ecological Interactions - Sun, Li; Lei, Yongjia; Li, Hui (Frontiers in Environmental Science, 2022)
This study focused on important factors including light intensity, light/dark cycles, and the biomass of algae/bacteria to explore the relationship between algae and bacteria, aiming to obtain the optimal performance in the algae–sludge membrane bioreactor (AS-MBR). It was found that 3000 lux was considered to be the appropriate light intensity that could improve algal biomass and nitrogen removal among the chosen light intensities. Further analysis of results indicated that a higher or lower light intensity could not simultaneously promote algal energy absorption and nitrifying bacterial activity. Moreover, the highest average growth rate of algae (0.16 mg/L d−1) and the removal efficiency of NH4+-N (96.4 ± 1.5%) were both observed during the 12-h light/12-h dark cycle, respectively. Meantime, the appropriate algal proportion would mitigate membrane fouling compared with the conventional MBR. The investigation of the mechanism suggested that light intensity, light–dark cycle, and algal proportion were significantly associated with algal photosynthesis (key proteins, chromophores, and nucleic acids), the characteristics of functional bacteria, and the underlying cognition of cell-to-cell signaling between algae and bacteria, which would further influence the reactor performance.